Risk Factors for One-Year Mortality in Elderly Patients Undergoing Surgery for Intertrochanteric Fracture - Chaiperm, Chayut; Athikraimongkol, Buncha; Parama; Narinsorasak, Thana (Royal Thai Air Force Medical Gazette, 2023)
Objective: To identify risk factors associated with one-year mortality following intertrochanteric hip fracture surgery in elderly patients. Methods: We collected data on elderly patients aged 60 years or older who underwent surgical internal fixation for intertrochanteric hip fractures at Bhumibol Adulyadej Hospital. We analyzed factors that may affect mortality rates using statistical analysis. Results: Of the population studied, 73.6% were female and 26.4% were male, with an average age of 78 years for males and 80 years for females. The majority of patients were classified as American Society of Anesthesiologists class II (68.1%) and had two joint diseases before treatment (38.9%). The study found that male patients had a 3.615 times higher risk of mortality compared to females. Patients with postoperative blood calcium levels less than 8 mg/dL had a 7 times higher mortality rate than those with levels greater than 8 mg/dL. Conclusion: Our study identified two significant risk factors associated with increased mortality rates in elderly patients undergoing intertrochanteric hip fracture surgery: male gender and postoperative blood calcium levels less than 8 mg/dL. These findings can help clinicians identify high-risk patients and optimize postoperative care to improve outcomes.